Edukasi dan Implementasi Effleurage Massage dengan Essential Oil Serai untuk Penurunan Nyeri Punggung Ibu Postpartum - Armika Leora Butar Butar; Eldesi Medisa Ilmawati; Indah Almaidah (Health Community Service, 2025)
Back pain is one of the most common complaints experienced by postpartum mothers, primarily due to changes in posture during pregnancy and the labor process. Non-pharmacological management, such as effleurage massage with the aid of essential oils, is believed to effectively reduce pain levels. This study aims to determine the level of back pain in postpartum mothers before and after the administration of effleurage massage using lemongrass and eucalyptus essential oils, and to analyze the effect of this therapy on reducing back pain at the Gambir Baru Public Health Center (Puskesmas). This study utilized a quantitative method with a pre-experimental one-group pretest-posttest design. The sample consisted of 30 postpartum mothers who met the inclusion criteria, selected using a total sampling technique. The pain measurement instrument used was the Wong-Baker FACES Pain Rating Scale (VAS) observation sheet. Effleurage massage combined with lemongrass and eucalyptus essential oils is proven effective in reducing back pain in postpartum mothers. This therapy can serve as an alternative non-pharmacological intervention in postpartum midwifery care.